THE EFFECTIVENESS OF FOOT EXERCISE AND HYDROTHERAPY ON BLOOD SUGAR LEVELS IN THE ELDERLY - Edy Nuswantara Putra; Erna Setiawati; Marijo Marijo; Yuswo Supatmo (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background: Elderly are susceptible to health problems due to decreased organ function such as increased blood sugar levels that are at risk for diabetes mellitus, so proper management is needed with physical activity. Foot exercise and hydrotherapy can be an alternative to physical activity for elderly to lower blood sugar levels.Objective: To determine the effectiveness of the combination of foot exercise with and without hydrotherapy on blood sugar levels in the elderly.Methods: Experimental study with parallel 3 groups pre and post-test design. Research subjects were 21 elderly, divided into control group (n=7), combination of foot exercises and hydrotherapy intervention group (n=7), and foot exercise intervention group (n=7). The intervention was done 3 times a week for 5 weeks. Blood sugar levels were measured using POCT.Results: There is no significant decrease in blood sugar levels from control group (p>0.05). There is significant decrease in blood sugar levels from foot exercise and hydrotherapy intervention group (p<0.05) and foot exercise intervention group (p<0.05). The difference in blood sugar levels showed significant results between foot exercise and hydrotherapy intervention group and control group (p=0.000) and between foot exercise intervention group and control group (p=0.004). There is no significant differences in blood sugar levels between foot exercise and hydrotherapy intervention group and foot exercise intervention group (p=0.112).Conclusion: Both foot exercise and hydrotherapy are effective in lowering blood sugar levels in the elderly.